"We noticed that suddenly the country has become full of MRI". Policy makers' views on diffusion and use of health technologies in Iran - Tishelman Carol; Palesh Mohammad; Fredrikson Sten; Jamshidi Hamidreza; Tomson Göran; Emami Azita (BMC, 2010)
Abstract Objective Uncontrolled proliferation of health technologies (HT) is one contributor to the increasing pressure on health systems to adopt new technologies. With limited resources, policy-makers encounter difficulties in fulfilling their responsibility to meet the healthcare needs of the population. The aim of this study is to explore how policy-makers' reason about the diffusion and utilization of health technologies in Iran using magnetic resonance imaging (MRI) and interferon beta as tracers. Method This qualitative exploration complements quantitative data generated in a research project investigating the diffusion and utilization of MRI and interferon beta in Iran. Qualitative semi-structured interviews were conducted with 13 informants in different positions and levels of authority in the Ministry of Health (MOH), University of Medical Sciences, Health Insurance Organizations, and Parliament. The data was analysed using the framework approach. Findings Although policy-makers appeared to be positive to health technology assessment (HTA), the processes of policy-making described by the interviewees did not seem to be based on a full understanding of this (discipline). Several obstacles to applying knowledge about HT and HTA were described. The current official plan for MRI adoption and diffusion in the country was said not to be followed, and no such plan was described for interferon beta. Instead, market forces such as advertising, and physician and consumer demand, appear to have strong influence on HT diffusion and use. Dual practice may have increased the induced demand and also reduced the supervision of the private sector by the MOH. Conclusion Management instability and lack of coordination in the MOH were found to be important obstacles to accumulation of knowledge and experience which, in turn, could have led to suboptimal managerial and policy-making processes. Furthermore marketing should be controlled in order to avoid creating unnecessary patient demands and negative influences on physicians' behavior.